Worlds within : National narratives and global connections in postcolonial writing - Cooppan, Vilashini (Cultural memory in the present., 2009)
This book tracks the changing forms of novels and nations against a long, postcolonial twentieth century. While globalization has sometimes been understood as superseding national borders, the book distances itself from before-and-after sequences in order to trace the intersection between national and global politics.